Survival after renal cell carcinoma metastasis to the thyroid: single center experience and systematic review of the literature - Beutner, Ulrich; Leowardi-Bauer, Christine; Bork, Ulrich; Lüthi, Cornelia; Tarantino, Ignazio; Pahernik, Sascha; Wente, Moritz N.; Büchler, Markus W.; Schmied, Bruno M.; Müller, Sascha A. (Thyroid, 2015)
Background: Renal cell carcinoma can metastasize to uncommon sites, for example, the thyroid gland where metastases are rarely found. To determine the patient survival and the time between cancer diagnosis and thyroid metastasis, we analyzed a large patient cohort from our hospital records and performed a systematic review.Patients and Methods: Patients diagnosed between 1978 and 2007 with thyroid metastases from renal cell carcinoma were retrospectively identified from the hospital database. A systematic literature search was performed for publications describing at least three cases of thyroid metastasis from renal cell carcinoma. Case data from the identified studies were collected and used to determine the survival data.Results: We identified 34 patients (19 females) from our hospital records with a mean age of 67 years (range, 33-79) when thyroid metastasis was diagnosed. Median time to primary metastasis after resection of renal cell carcinoma was 6.5 years (range, 0-25) with a single case of synchronous metastasis. Median survival after primary metastasis was 4.7 years (95% confidence interval [CI]: 1.8-7.6). The systematic review included 32 studies with 285 patients. Case data could be extracted for 202 patients. Median time to thyroid metastasis (without synchronous cases) was 8.8 years (95% CI: 7.5-10.1). Median actuarial survival after thyroid metastasis was 3.4 years (95% CI: 2.2-4.6). Total thyroidectomy was not associated with a better survival compared to partial thyroidectomies.Conclusions: Time to thyroid metastasis of renal cell carcinoma can be very long, and survival after thyroidectomy is favorable compared to metastasis to other sites.
Gesehen am 25.05.2020